Divorce Contribution During the Covid-19 Pandemic in Banjarmasin City - Muzainah, Gusti; Faridh, Miftah; Hasan, Ahmadi (Kawanua International Journal of Multicultural Studies, 2023)
The Covid-19 epidemic has influenced numerous facets of human existence. There are a large number of layoffs which has a negative economic impact on the family. According to data made accessible by the Banjarmasin Religious Court, the divorce rate increased from 13729 cases in 2020 to 1652 cases in 2021. This study intended to identify the contribution to the cause of divorce in Banjarmasin during the Covid-19 pandemic. The method employed was empirical legal research, and the approaches were legal sociology and legal psychology. The results revealed that the covid-19 pandemic has contributed to the rising divorce rate. Economic issues, domestic abuse, and the presence of a third party are the leading causes of divorce. In addition, this study indicated that husbands were victims of domestic violence.